2019
DOI: 10.1021/acsami.9b17468
|View full text |Cite
|
Sign up to set email alerts
|

Highly Monochromatic Electron Emission from Graphene/Hexagonal Boron Nitride/Si Heterostructure

Abstract: In this work, a planar electron emission device based on a graphene/hexagonal boron nitride (h-BN)/n-Si heterostructure is fabricated to realize highly monochromatic electron emission from a flat surface. The h-BN layer is used as an insulating layer to suppress electron inelastic scattering within the planar electron emission device. The energy spread of the emission device using the h-BN insulating layer is 0.28 eV based on the full-width at half-maximum (FWHM), which is comparable to a conventional tungsten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 51 publications
1
26
0
Order By: Relevance
“…In our recent study, we demonstrated the electron emission from a graphene/h-BN/n-Si heterostructure. 32 This result indicates that h-BN can be used as the insulating layer of planar-type electron emission devices. High-quality graphene can be epitaxially grown on the h-BN surface because h-BN has a similar crystal structure to that of graphene.…”
Section: ■ Experimental Sectionmentioning
confidence: 90%
See 2 more Smart Citations
“…In our recent study, we demonstrated the electron emission from a graphene/h-BN/n-Si heterostructure. 32 This result indicates that h-BN can be used as the insulating layer of planar-type electron emission devices. High-quality graphene can be epitaxially grown on the h-BN surface because h-BN has a similar crystal structure to that of graphene.…”
Section: ■ Experimental Sectionmentioning
confidence: 90%
“…The energy spectra of the emitted electrons of the GOS structure were obtained using a hemispherical electron energy analyzer. The detailed measurement set-up of the electron energy distributions of the GOS device is described in a previous paper …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Measuring the electron transparencies at lower energies is difficult due to the strong electrostatic field needed to extract electrons by field emission. Planar graphene devices have been demonstrated for low-energy electron field emission measurements from graphene; however these devices do not provide an independent measure of electron transmission through graphene membranes with different number of layers [14]. In this work, we instead use atomically sharp Si emitters with self-aligned gates to extract electrons at voltages of less than 20 V as a separate electron source.…”
Section: Introductionmentioning
confidence: 99%
“…The development of next-generation electron sources is crucial for improving the efficiency of electron microscopes. Materials such as strained superlattice GaAs/GaAsP semiconductor photocathodes [1], graphene/h-BN/n-Si heterostructure planar electron emission devices [2], Co2MnGa❬100❭ tip [3], LaB 6 ❬100❭ nanowire [4], CeB 6 ❬310❭ tip [5], and amorphous carbon-coated metal tip [6,7] have been investigated in this direction. One of the important factors that determines the efficiency (probe diameter or coherence) of an electron optical device is the brightness of the electron source.…”
Section: Introductionmentioning
confidence: 99%